PENGENALAN KARAKTERISTIK WIRAUSAHA PADA UKM - Rodhiah; Lerbin Roberto Aritonang R. (Transpublika Publisher, 2021)
Growing small and medium-sized enterprises (SMEs) with entrepreneurial characteristics is crucial for sustaining Indonesia's economy. This study aims to assist business owners in understanding the significance of possessing entrepreneurial traits in achieving business success. The activity took place at LaZiesha Kitchen, a culinary business in Jambi specializing in Food and Beverage, with popular products including crispy getuk and rainbow onde-onde. Initial observations of the partners revealed a lack of entrepreneurial characteristics, resulting in a lack of entrepreneurial success. The proposed method for the activity was training and socialization of entrepreneurial characteristics, covering topics such as understanding entrepreneurial traits and their impact on business success. The delivery of materials during the activity proceeded smoothly, with enthusiastic partners actively engaging in discussions with the PKM team. Evaluation results indicate that 90% of the partners comprehended the delivered content and increased their knowledge regarding the essential characteristics required for entrepreneurship.